2021
DOI: 10.1093/arclin/acab023
|View full text |Cite
|
Sign up to set email alerts
|

Validation of HVLT-R, BVMT-R, and RBANS Learning Slope Scores along the Alzheimer’s Continuum

Abstract: Background The learning ratio (LR) is a novel learning slope score that has been developed to reduce the inherent competition between the first trial and subsequent trials in traditional learning slopes. In essence, the LR is the number of items learned after the first trial divided by the number of items yet to be learned. Criterion and convergent validation of this LR score is warranted to understand its sensitivity along the Alzheimer’s disease (AD) continuum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Although clinical applications of LR within the ANB require further investigation, it is encouraging that prior research in clinical samples using LR methodology in other learning tests has shown that LR differentiates between those with and without neurocognitive impairments (Spencer et al, 2020;Hammers et al, 2021aHammers et al, , 2021b with receiver operating characteristics area under the curve (AUC) in the acceptable to excellent range. Further, LR scores correlate significantly with other neuropsychological tests of memory, Alzheimer's-related biomarkers, hippocampal volume, and genetic risk for Alzheimer's (Hammers et al, 2021b(Hammers et al, , 2021cSpencer et al, 2020). Similarly, we would expect LR scores from the ANB to show similar clinical utility, but additional research is needed.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Although clinical applications of LR within the ANB require further investigation, it is encouraging that prior research in clinical samples using LR methodology in other learning tests has shown that LR differentiates between those with and without neurocognitive impairments (Spencer et al, 2020;Hammers et al, 2021aHammers et al, , 2021b with receiver operating characteristics area under the curve (AUC) in the acceptable to excellent range. Further, LR scores correlate significantly with other neuropsychological tests of memory, Alzheimer's-related biomarkers, hippocampal volume, and genetic risk for Alzheimer's (Hammers et al, 2021b(Hammers et al, , 2021cSpencer et al, 2020). Similarly, we would expect LR scores from the ANB to show similar clinical utility, but additional research is needed.…”
Section: Discussionmentioning
confidence: 93%
“…Using the RBANS List Learning and Story Memory subtests, Spencer et al (2020) demonstrated psychometric superiority of LR relative to the conventional RLS method. Follow-up investigations comparing LR with RLS suggest LR is more robustly correlated with traditional memory and learning measures, provides superior diagnostic differentiation of clinical groups, and is correlated more strongly with relevant neuroanatomic (i.e., hippocampal volume) and other biomarker data such as ApoE4 status (Hammers et al, 2021a(Hammers et al, , 2021b(Hammers et al, , 2021c. Recent studies have developed LR aggregates by combining learning slope measures (i.e., List Learning and Story Memory on the RBANS), stabilizing resultant metrics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By eliminating confounds from ceiling effects, the LR may result in stronger associations and predictive ability for clinically relevant outcomes than the RLS, which typically produces weak to null findings when evaluated in the context of demographic characteristics and other performance characteristics. 10 When both scores are directly compared, LR performs equal to or better than RLS for correlations with memory tests, 3,17,18,22,23 diagnostic discrimination, 3,18,23 as well as other known risk factors for AD, including hippocampal volume, AD-specific biomarkers, and APOE4 status. [22][23][24] Thus, the LR score is a relatively new but promising metric that warrants additional examination, particularly in the context of detecting AD using non-invasive assessment methods.…”
Section: Lr = Final Trial Performance − First Trial Performance Maxim...mentioning
confidence: 99%